2010
DOI: 10.1371/journal.pone.0013137
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human Antigen-Specific Monoclonal IgM Antibodies Using Vaccinated “Human Immune System” Mice

Abstract: BackgroundPassive transfer of antibodies not only provides immediate short-term protection against disease, but also can be exploited as a therapeutic tool. However, the ‘humanization’ of murine monoclonal antibodies (mAbs) is a time-consuming and expensive process that has the inherent drawback of potentially altering antigenic specificity and/or affinity. The immortalization of human B cells represents an alternative for obtaining human mAbs, but relies on the availability of biological samples from vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
57
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 43 publications
(66 reference statements)
4
57
0
1
Order By: Relevance
“…Plasma was harvested from HSC-NRG mice 20 wk after reconstitution and screened by ELISA for the presence of total human IgM an total human IgG as described elsewhere (21). Total IgM and IgG determination was performed by coating 96-well plates either with AffiniPure F(ab9) 2 fragment goat anti-human IgM (Fc5m specific; Jackson ImmunoResearch Laboratories) or AffiniPure goat anti-human IgG (Fcg fragment specific; Jackson ImmunoResearch Laboratories) at a concentration of 1.2 mg/ml.…”
Section: Ig Production In Hsc-nrg Micementioning
confidence: 99%
“…Plasma was harvested from HSC-NRG mice 20 wk after reconstitution and screened by ELISA for the presence of total human IgM an total human IgG as described elsewhere (21). Total IgM and IgG determination was performed by coating 96-well plates either with AffiniPure F(ab9) 2 fragment goat anti-human IgM (Fc5m specific; Jackson ImmunoResearch Laboratories) or AffiniPure goat anti-human IgG (Fcg fragment specific; Jackson ImmunoResearch Laboratories) at a concentration of 1.2 mg/ml.…”
Section: Ig Production In Hsc-nrg Micementioning
confidence: 99%
“…Although antigenspecific human IgM antibody responses are generated, the achievement of affinity maturation and class-switching from the IgM to the IgG isotype has been particularly difficult. 5,6 Several reports demonstrated that antigen-specific human IgG can be detected in humanized mice by enzyme-linked immunosorbent assay (ELISA). 7,8 The B-cell response was nevertheless not robust and the scarcity of IgG 1 memory B cells makes them extremely difficult to be identified and isolated.…”
Section: Introductionmentioning
confidence: 99%
“…There have been major recent improvements in the way in which genetic information to encode Ag-specific mAbs can be obtained directly from human B cells (3)(4)(5). However, such approaches are largely restricted to Ags such as infectious agents where individuals mounting a specific immune response can be identified and provide a source of Ag-specific B cells.…”
mentioning
confidence: 99%